Added value of aortic pulse wave velocity index for the detection of coronary heart disease by elective coronary angiography. (2nd November 2019) - Vallée, Alexandre; Zhang, Yi; Protogerou, Athanase; Safar, Michel E.; Blacher, Jacques
Abstract: Background: Non-invasive tests leading to elective coronary angiography (CAG) have low diagnostic yield for obstructive coronary heart disease (CHD). Aortic stiffness, an independent predictor of CHD events can be easily measured by pulse wave velocity (PWV). We aimed at retrospectively evaluating the diagnostic accuracy PWV index to detect CHD in consecutive patients with suspected CHD that underwent CAG. Method: In population of 86 healthy patients with available PWV data, a theoretical PWV was derived. In different population of 62 individuals who underwent CAG for suspected CHD, PWV index was calculated as index [(measured PWV – theoretical PWV)/theoretical PWV]. Logistic regression and comparisons between ROC curves were used to add value of CAG indication performance of PWV index. Results: Out of 62, seventeen patients presented obstructive CHD and 22 patients had non-obstructive CHD. PWV index and severity of CHD were positively correlated ( p  < 0.0001). After applying several models that included classical CHD predictor, the higher performance to detect abnormal CAG was obtained with the combined classifier PWV index/carotid plaque with 87% sensitivity, 93% specificity, 0.92 accuracy and 0.31 threshold. To detect obstructive CAG, individual classifier PWV index presents 94% sensitivity, 91% specificity, 0.95 accuracy and 0.46 threshold. Conclusion: PWV index is individualized approach that optimizes CHD diagnostic strategies and thus might be clinically useful for reducing the rate of unnecessary invasive CAG.